2003
DOI: 10.4049/jimmunol.171.12.6788
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monocyte Chemotactic Protein-1/CC Chemokine Ligand 2 on γδ T Lymphocyte Trafficking during Inflammation Induced by Lipopolysaccharide orMycobacterium bovisBacille Calmette-Guérin

Abstract: γδ T lymphocytes are involved in a great variety of inflammatory and infectious responses. However, the mechanisms by which γδ T lymphocytes migrate to inflamed sites are poorly understood. In this study we investigate the role of monocyte chemotactic protein (MCP)-1 in regulating γδ T cell migration after LPS or Mycobacterium bovis bacille Calmette-Guérin (BCG) challenge. LPS-induced γδ T cell influx was significantly inhibited by either pretreatment with dexamethasone or vaccinia virus Lister 35-kDa chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 58 publications
5
50
1
1
Order By: Relevance
“…MCP-1 binds to and activates leukocytes preferentially through CCR2 (44,45). Our results confirmed that CCR2 was expressed on ␥␦ T cells induced by DXS2 protein.…”
Section: Discussionsupporting
confidence: 76%
“…MCP-1 binds to and activates leukocytes preferentially through CCR2 (44,45). Our results confirmed that CCR2 was expressed on ␥␦ T cells induced by DXS2 protein.…”
Section: Discussionsupporting
confidence: 76%
“…In addition to being present on inflamed endothelium, E-selectin is constitutively expressed on dermal microvessels making it likely that LN emigrant Vγ4 + Vδ4 + γδT cells are able to undergo CLA-E-selectin-supported rolling interactions with healthy dermal endothelium (33). The contribution of CCR2 to γδT-cell accumulation in the skin adds to data showing a role for CCR2 in γδT-cell homing to the pleural cavity (34).…”
Section: Discussionmentioning
confidence: 84%
“…3D). CCL-2/MCP-1 is crucial for the recruitment of innate immune effectors, including ␥␦ T cells (13,36). A flow cytometric analysis shows that a higher percentage of CD3 ϩ T cells was detected in the visceral fat pads of MC159 transgenic mice (Fig.…”
Section: Mc159 Transgenic Mice Exhibited Enhanced Control Of Vv Infecmentioning
confidence: 99%